Balajad as a Medium for Digital Cultural Da'wah: Internalizing Islamic Values through Traditional Arts - Irma Nuhaza; Ayu Faiza Algifahmy; M Abdul Rahman Hakim (The Future of Education Journal, 2025)
This study aims to analyze the integration of Islamic values in cultural da'wah in the digital era carried out by the Balajad group through the Balajad_Official YouTube channel. As a cultural arts group, Balajad utilizes the medium of music and tradition as a means to convey inclusive and humanist Islamic messages. In the context of digital space, the da'wah they build is not only informative, but also forms a close communication relationship with the public. This research uses a descriptive qualitative approach with visual and content analysis techniques, to understand the visualization and content of Islamic values-based da'wah in Balajad's videos. Data were obtained from a number of selected videos that became the focus of the research, with an emphasis on how values such as ta'awun (helping), tawadhu' (humble), ukhuwah Islamiyah, tawhid, optimism, and gratitude are integrated in their cultural da'wah narrative. The Balajad_Official channel is positioned as a strategic medium to build a culturally friendly Islamic image, respond to contemporary issues, and strengthen emotional ties with digital audiences. The results show that Balajad's success in delivering relevant, communicative, and adaptive da'wah messages to plural societies is largely determined by the integration of Islamic values into cultural art formats. This study makes an important contribution to the development of Islamic Religious Education and Islamic Broadcasting Communication, especially in understanding contextual and effective cultural da'wah strategies in the digital era.